2009
DOI: 10.1016/j.bpj.2008.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Changes in the Structure and Function of the Kinesin-Microtubule Complex

Abstract: Kinesin-1 is an ATP-driven molecular motor that "walks" along a microtubule by working two heads in a "hand-over-hand" fashion. The stepping motion is well-coordinated by intermolecular interactions between the kinesin head and microtubule, and is sensitively changed by applied forces. We demonstrate that hydrostatic pressure works as an inhibitory action on kinesin motility. We developed a high-pressure microscope that enables the application of hydrostatic pressures of up to 200 MPa (2000 bar). Under high-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 58 publications
(87 reference statements)
4
46
0
Order By: Relevance
“…All assays were repeated with at least three different cultures. In addition, we confirmed that the applied pressure did not significantly change the physical characters, such as temperature, viscous drag, and pH, of the solution (20,32). Figure 1a shows a schematic diagram of our high-pressure microscope (32).…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…All assays were repeated with at least three different cultures. In addition, we confirmed that the applied pressure did not significantly change the physical characters, such as temperature, viscous drag, and pH, of the solution (20,32). Figure 1a shows a schematic diagram of our high-pressure microscope (32).…”
Section: Methodssupporting
confidence: 63%
“…Hydrostatic pressure is one of the physical stimuli that characterize the environment of microorganisms (16,17), and the pressure-induced changes could be visualized by high-pressure microscopy (18)(19)(20)(21)(22). E. coli is a representative research target for studying the mechanism by which hydrostatic pressure affects bacterial physiology, such as transmembrane transport (23,24), protein and nucleic acid synthesis (25), enzymatic function (26), cell division (22,27,28), and growth (27)(28)(29).…”
mentioning
confidence: 99%
“…There have been exciting recent developments in design and use of high pressure optical microscopy systems, allowing bright field (Frey et al, 2006;Reck et al, 1998), polarizing (Reck et al, 1998;Salmon, 1975;Salmon and Ellis, 1975) and fluorescence (Nicolini et al, 2006a;Nishiyama et al, 2009;Vass et al, 2010) microscopy, at pressures as high as 700 MPa (Vass et al, 2010). A number of these cells have again been based on similar design principles to the soft matter SAXS cells described above with the pressure being held by rubber or metal o-ring type seals (Reck et al, 1998).…”
Section: Optical Soft Matter Cellsmentioning
confidence: 96%
“…According to Nishiyama et al 25 pressure is directly proportional to strength even thought they are different measures. Many studies 11,26,27 with pressure manometers, also known as perineometers, compared the PFM pressure of continent and incontinent women and found a higher pressure in continent women corroborating with the results of the PFM anteroposterior active strength obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%